Aphids as crop pests - Van Emden, H. F. (Helmut Fritz); Harrington, Richard, 1955- (CABI, 2017)
This book contains 33 chapters focusing on taxonomy, population dynamics, biological characteristics, feeding behaviour, crop damage, disease transmission, control, monitoring and forecasting of aphid pests of various crops. The efficacy of various methods (biological, chemical, cultural and host resistance) and their combinations for the control of these aphid pests are also discussed